(untitled) (Global Journal of Management and Business Research, 2018)
Presence of globalization enabled a competitive business environment where career development is becoming a hot topic among every professional. The importance of the Human Resource (HR) professionals in the top of the ladder is prominence with enhancing focus on people-oriented culture. Hence, the purpose of the study is to whether perceived career barriers are associated with the career development of HR professionals in the Sri Lankan context. The study identified perceived barriers namely; lack of culture fit, excluded from informal, lack of mentoring, poor organizational career management processes, difficulty of getting developmental assignments, and the difficulty of obtaining opportunities for geographic mobility. Two hundred sixty-four (264) questionnaires were collected, which developed using standard measures and analyzed using multiple linear regression and hierarchical regression to identify the significant impact of perceived barriers on career development. Findings revealed that there is a negative impact of perceived barriers on career development and difficulty getting developmental assignment is the most dominant perceived barriers, which hinder career development of HR professionals to climb the top of the corporate ladder.